LEAN LOGISTICS - Wronka, Anna (Journal of Positive Management, 2017)
Purpose: The aim of the article is to present the key assumptions of Lean Management, with particular focus on the components of Lean Management System and the assessment matrix of implementation the Lean concept. In addition, Author demonstrates the applicability of Lean paradigms to improve the logistics area, as well as to improve the functioning of supply chains, especially by using methodology which links Six Sigma and Lean ideas as well as Agile approach. This paper except theoretical analysis presents lean logistics application in practice. Short case study is developed on basis of best lean logistics practices of company from B2B market. Methodology: The used research approach was the detailed analysis of logistics international literature and case study based on internal documents and interviews with lean managers from international company. Findings: Emphasizing the multidimensionality of the concept, Author indicates potential areas of integration Lean with other tools and strategies used in modern businesses management, like Six Sigma or Agile approach. Additionally article presents practical application of Lean in logistics.